PENGARUH PENGELUARAN PEMERINTAH DAN INVESTASI SWASTA TERHADAP TINGKAT KEMISKINAN DI JAWA TENGAH : PENDEKATAN REGRESI DATA PANEL - Andjar Prasetyo (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2015)
This research aims to find out and analyze the consumption expenditures and investment expenditures of government spending as well as the realization of private sector investment. Result of the analysis are then used to determine its effects on the poverty rate in 35 districts of central java province in 2008 in the period up to the year 2013 separately, methods of analysis using regression data panel because the data in the form of cross section and time of series by the method of fixed effect model. The three main variables of comsuption expenditures, investment expenditures and realization private sector investment. In this study the consumption expenditures specifed in goods and services expenditures , grants expenditures , social assistance expenditure =s, while specified in order to nvestment expenditures are tools and machinery expenditures, buildings expenditures, irigation and road network expenditures other fixed assets expenditures. The development of the hypothesis of this research is thought to have negative influece or relationship upside-down between government spending and private investment towards the realization of the poverty rate in 35 District Of Central Java provience in 2008 year period up to the year 2013. From the results of the test precision of Ftest value model of 97,98 percent on levels of poverty. The influece of government spending and private investment toward the realization of poverty levels obtained equiation : Kmsknan = 158,431796626-1,4886 Bljbrg – 1,8240 Bljhbah + 2,4067 Bansos-2,0880 Peralmes -5,3047 Banged + 3,09406 Jairjar – 2,93462 Asttl = 5.9541 Reinsws. Variable goods and services expenditures, grants expenditures, mechine expenditures, building expenditures, other fixed assets expenditures, realization of private sector investment, have inverted the relationship to the level of poverty, howewer social assistence expenditures, the streets irigation network expenditures, and the realization of private sector investment has a positive influence. Variables that have a negative relationship needs to be constantly improved and variables have positive relationship need to do more research.